Sistem Perbankan Syariah di Indonesia: Landasan Teologis, Regulasi Nasional, dan Tantangan Kepatuhan Syariah - Ghazyan Hidzyam Haqqani; Santana Suryapringgana; M. Aldo Dellano (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the Islamic banking system in Indonesia by focusing on the interrelationship between theological foundations, national regulation, and challenges of Sharia compliance in operational practice. The theological basis of Islamic banking is rooted in the principles of Islamic law that emphasize justice, public benefit (maslahah), and balance in the legal relationship between banks and customers. These principles have been accommodated within the national legal system through Islamic banking regulations and supervisory mechanisms implemented by state authorities and the Sharia Supervisory Board. This research employs a normative legal research method using statutory and conceptual approaches to analyze the conformity between Sharia norms and positive law. The findings indicate that national regulation has provided legal certainty and a relatively comprehensive supervisory framework; however, it continues to face challenges related to the consistency of Sharia compliance, risk management, and adaptation to financial technological innovation. Strengthening governance, internalizing Sharia values, and harmonizing regulatory frameworks are therefore essential to ensuring the sustainability of Islamic banking within the national financial system.